South African Acrothoracica (Crustacea: Cirripedia) - Botha, Thomas P.a.; Griffiths, Charles L. (Zootaxa, 2021)
Prior to this review, only three publications, all species descriptions published over 50 years ago, had focussed on South African acrothoracicans. We collected samples from three of South Africa’s major marine ecoregions (Benguela, Agulhas and Natal) and used these to produce a revised account of the known regional fauna. This includes a key to known South African acrothoracicans and a systematic account of the species, each description being accompanied by scanning electron and light microscopy images. The number of known South African acrothoracicans is increased from four to eight species, with three new distribution records and two new species added to the fauna, while one existing record is determined to be a nomen nudum. Although this represents a doubling of the known regional acrothoracican fauna, much more remains to be explored, and further research in deeper waters and examination of other potential hosts (such as corals and hermit crabs) are likely to reveal many additional taxa.